High temperature promotes auxin-mediated hypocotyl elongation in Arabidopsis - Gray, William M. (The National Academy of Sciences, 1998)
Physiological studies with excised stem segments have implicated the plant hormone indole-3-acetic acid (IAA or auxin) in the regulation of cell elongation. Supporting evidence from intact plants has been somewhat more difficult to obtain, however. Here, we report the identification and characterization of an auxin-mediated cell elongation growth response in Arabidopsis thaliana. When grown in the light at high temperature (29°C), Arabidopsis seedlings exhibit dramatic hypocotyl elongation compared with seedlings grown at 20°C. This temperature-dependent growth response is sharply reduced by mutations in the auxin response or transport pathways and in seedlings containing reduced levels of free IAA. In contrast, mutants deficient in gibberellin and abscisic acid biosynthesis or in ethylene response are unaffected. Furthermore, we detect a corresponding increase in the level of free IAA in seedlings grown at high temperature, suggesting that temperature regulates auxin synthesis or catabolism to mediate this growth response. Consistent with this possibility, high temperature also stimulates other auxin-mediated processes including auxin-inducible gene expression. Based on these results, we propose that growth at high temperature promotes an increase in auxin levels resulting in increased hypocotyl elongation. These results strongly support the contention that endogenous auxin promotes cell elongation in intact plants.